Chest injuries in a district general hospital. - Thompson, G. A. (Royal College of Surgeons of England, 1982)
Patients with chest injuries requiring admission to the Kent and Canterbury Hospital over a period of one year have been reviewed. Good survival figures are possible when these patients are managed by general surgeons and anaesthetists once the initial traumatic insult and immediate resuscitation period are survived. Among the 54 patients admitted there were 11 deaths, of which 10 occurred within a few hours of the patient's reaching hospital. It seems unlikely that even with specialist facilities the outcome would have been different in these 10 patients. Provided that a combination of experienced surgical and anaesthetic teams supported by intensive care facilities are mobilised quickly enough the absence of specialised cardiothoracic expertise is not important.